Distance From Cervicovaginal Junction to Anterior Peritoneal Reflection Measured During Vaginal Hysterectomy. Issue 4 (October 2016) - Balgobin, Sunil; Hamid, Cherine A.; Carrick, Kelley S.; Montoya, T. Ignacio; Schaffer, Joseph I.; Corton, Marlene M.
Abstract : OBJECTIVE: To quantify the distance of the dissection plane from the cervicovaginal junction to the anterior peritoneal reflection for vaginal hysterectomy. METHODS: This is a descriptive study examining the dissection plane for anterior colpotomy in 22 surgical patients undergoing vaginal hysterectomy and in nine cadaver specimens. Intraoperatively, the distance from the vaginal incision to the anterior peritoneal reflection was measured on the uterus after removal. In nine of these patients, this distance was also measured before anterior peritoneal incision. Embalmed cadavers with intact pelvic viscera were dissected and the distance of the same dissection plane was measured. RESULTS: Median (interquartile range) surgical patient age was 51.5 (42–63) years and the main surgical indications were abnormal uterine bleeding and pelvic organ prolapse. In these patients, the median (interquartile range) distance from cervicovaginal incision to anterior peritoneal reflection was 3.4 (2.6–3.7) cm. In cadavers, the median (interquartile range) age was 81 (72–86) years with a measured distance of 2.7 (2.4–2.9) cm. CONCLUSION: When performing a vaginal hysterectomy, surgeons can expect a median (range) dissection distance of 3.4 (1.8–4.6) cm from initial incision to the peritoneal reflection for anterior colpotomy. Abstract : The distance from the cervicovaginal junction to the anterior peritoneal reflection measured during vaginal hysterectomy is approximately 3.4 cm.Supplemental Digital Content is Available in the Text.